2017
DOI: 10.1007/s40268-016-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Topiroxostat on Renal and Endothelial Function in A Patient with Chronic Kidney Disease and Hyperuricemic Arteriolopathy: A Case Report

Abstract: Hyperuricemia is associated with the progression of chronic kidney disease (CKD) and cardiovascular diseases. Topiroxostat, a selective xanthine oxidase inhibitor, effectively reduces serum uric acid (UA) levels and urinary albumin excretion (UAE) in CKD patients. A 50-year-old Japanese man was referred to our hospital due to albuminuria and hyperuricemia, and renal biopsy showed a typical hyperuricemic arteriolopathy. Treatment with topiroxostat decreased serum UA levels (9.2 mg/dL at baseline to 6.4 mg/dL af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kawamorita et al [28] demonstrated that the renoprotective effects of topiroxostat could be attributed to its potential anti-oxidative action as demonstrated by inhibiting nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in concert with suppression of intracellular uric acid production. In addition, it is also suggested that topiroxostat improves vascular endothelial function [7]. Recently, Kuki et al [15] demonstrated that topiroxostat reduced not only serum uric acid level, but also urinary albumin excretion, serum hsCRP level, and plasma BNP level in patients with hyperuricemia at high risk for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawamorita et al [28] demonstrated that the renoprotective effects of topiroxostat could be attributed to its potential anti-oxidative action as demonstrated by inhibiting nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in concert with suppression of intracellular uric acid production. In addition, it is also suggested that topiroxostat improves vascular endothelial function [7]. Recently, Kuki et al [15] demonstrated that topiroxostat reduced not only serum uric acid level, but also urinary albumin excretion, serum hsCRP level, and plasma BNP level in patients with hyperuricemia at high risk for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike allopurinol, topiroxostat has shown renoprotective effects as demonstrated by the reduction of urinary albumin excretion, and thus can also be used without dose reduction in patients with mild to moderate renal dysfunction [6]. In addition, it is also suggested that topiroxostat ameliorates impaired vascular endothelial function beyond the uric acid lowering action [7]. These pharmacological actions of topiroxostat lead us to the hypothesis that this drug could have superior effects to allopurinol for patients with chronic heart failure and hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%